DOI: 10.31274/etd-180810-5399
|View full text |Cite
|
Sign up to set email alerts
|

Team-based learning in an undergraduate capstone course: Examining the effectiveness of a learner-centered instructional method for farm management and operation students

Abstract: method is warranted with particular attention to long-term outcomes and skill attainment. It is recommend that TBL be implemented in other courses within colleges of agriculture to further examine its utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
(152 reference statements)
0
1
0
Order By: Relevance
“…Although there are varying viewpoints on the validity of learning styles (Kirschner, 2017;Pashler et al, 2008;Simmonds, 2014), research has generated many questions in higher education institutions (HEI) regarding how to effectively educate an increasing number of undergraduate students with differing learning preferences to prepare them for professional life (Dunne & Rawlins, 2000). As HEI enrollment and the prevalence of social constructivist theory in higher education has expanded, team-based and collaborative learning theories have emerged to accommodate student learning and application of course content in larger university classes (Doolittle & Camp, 1999;McCubbins, 2016;Michaelsen et al, 2004). Koles et al (2010) showed that team-based learning can improve student performance on exam questions, improve overall grades, and have a positive impact on students' learning.…”
mentioning
confidence: 99%
“…Although there are varying viewpoints on the validity of learning styles (Kirschner, 2017;Pashler et al, 2008;Simmonds, 2014), research has generated many questions in higher education institutions (HEI) regarding how to effectively educate an increasing number of undergraduate students with differing learning preferences to prepare them for professional life (Dunne & Rawlins, 2000). As HEI enrollment and the prevalence of social constructivist theory in higher education has expanded, team-based and collaborative learning theories have emerged to accommodate student learning and application of course content in larger university classes (Doolittle & Camp, 1999;McCubbins, 2016;Michaelsen et al, 2004). Koles et al (2010) showed that team-based learning can improve student performance on exam questions, improve overall grades, and have a positive impact on students' learning.…”
mentioning
confidence: 99%